Pengaruh Tingkat Pendidikan Dan Pengalaman Kerja Terhadap Kinerja Karyawan Departemen Bottom Spray Painting Pada PT Chang Shin Karawang - Merry Rahmalia; Sungkono Sungkono; Maman Mulya Karnama (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The study aims to determine how the level of education, work experience and employee performance at PT Chang ShinKarawang, determine the influence of education level on employee performance and the influence of work experience on employee performance at PT Chang Shin Karawang. The method used is kuantitatif with a population of employees of PT Chang Shin department bottom spray painting which amounts to 50 people. A sample of 44 respondents was taken by the Slovin method. Analysis using PLS with the help of SmartPLS. The results showed that the level of education wasin the fairly high category, work experience was in the high category, and employee performance was in the fairly highcategory. The level of education has a positive and significant influence on employee performance at PT Chang Shin Karawang and work experience has a positive and significant influence on employee performance at PT Chang ShinKarawang Keywords: Education Level, Work Experience and Employee Performance